Anodic TiO2 nanotubes: double walled vs. single walled - Liu, Ning; Mirabolghasemi, Hamed; Lee, Kiyoung; Albu, Sergiu; Tighineanu, Alexei; Altomare, Marco; Schmuki, Patrik (Faraday Discussions, 2013)
Electrochemical formation of self-organized TiO2 nanotube layers has been a highly active research field for more than 10 years. In the present manuscript we investigate the formation of two distinctly different anodic TiO2 nanotube morphologies, `single walled' and `double walled' tubes, which are formed mainly depending on the nature of the anodization electrolyte. While the widest used electrolytes are ethylene glycol (EG) based, forming double walled structures, tubes formed in dimethyl sulfoxide (DMSO) based electrolytes show a single tube walled morphology. Here we provide reasons for the formation of double walled tubes, characterize tubes for their composition, structure and certain properties, and give measures to suppress or minimize double wall formation. Except for the fact that in DMSO single walled tubes are formed, we also show that they grow sufficiently slowly to allow partial crystallization of the tubes during growth – this, in turn drastically influences their electronic properties. Finally we discuss the effects and potential consequences of double or single wall growth for TiO2 nanotube applications.
EAM Import::2019-03-13

Controlling the Adsorption Kinetics via Nanostructuring: Pd Nanoparticles on TiO2 Nanotubes - Honciuc, Andrei; Laurin, Mathias; Albu, Sergiu; Sobota, Marek; Schmuki, Patrik; Libuda, Jörg (Langmuir, 2010)
Activity and selectivity of supported catalysts critically depend on transport and adsorption properties. Combining self-organized porous oxide films with different metal deposition techniques, we have prepared novel Pd/TiO2 catalysts with a new level of structural control. It is shown that these systems make it possible to tune adsorption kinetics via their nanostructure. Self-organized TiO2 nanotubular arrays (TiNTs) prepared by electrochemical methods are used as a support, on which Pd particles are deposited. Whereas physical vapor deposition (PVD) in ultrahigh vacuum (UHV) allows us to selectively grow Pd particles at the tube orifice, Pd/TiNT systems with homogeneously distributed Pd aggregates inside the tubes are available by particle precipitation (PP) from solution. Both methods also provide control over particle size and loading. Using in-situ infrared reflection absorption spectroscopy (IRAS) and molecular beam (MB) methods, we illustrate the relation between the nanostructure of the Pd/TiNT systems and their adsorption kinetics. Control over the metal nanoparticle distribution in the nanotubes leads to drastic differences in adsorption probability and saturation behavior. These differences are rationalized based on differences in surface and gas phase transport resulting from their nanostructure. The results suggest that using carefully designed metal/TiNT systems it may be possible to tailor transport processes in catalytically active materials.

Current dependent formation of PEDOT inverse nanotube arrays - Kowalski, Damian; Albu, Sergiu; Schmuki, Patrik (RSC Advances, 2013)
PEDOT nanostructures with distinct patterns can be formed by means of electrodeposition in titania nanotubes. The deposition process critically depends on the current protocol, leading to selective filling of the inner and/or outer space of the tubes. The approach allows for synthesis of vertically aligned PEDOT–titania composites or polymer nanostructures in the form of PEDOT inverse-nanotube-arrays and PEDOT nanopore-arrays.
EAM Import::2019-03-13

Excited state properties of anodic TiO2 nanotubes - Kahnt, Axel; Oelsner, Christian; Werner, Fabian; Guldi, Dirk Michael; Albu, Sergiu; Kirchgeorg, Robin; Lee, Kiyoung; Schmuki, Patrik (Applied Physics Letters, 2013)
Charge carriers, that is, holes as well as trapped and "free" electrons were investigated by means of time resolved spectroscopy in anodic TiO nanotubes that were heat treated at different temperatures. The lifetimes of the charge carrier were compared with those generated in reference layers of Solaronix Ti-Nanoxide D and Degussa P25 nanoparticles. Remarkably long lived "free" electrons were only noted in the TiO nanotubes. These findings have significance in view of any photoelectrochemical applications of TiO nanotubes. © 2013 2013 Author(s).

High aspect ratio, self-ordered iron oxide nanopores formed by anodization of Fe in ethylene glycol/NH4F electrolytes - Albu, Sergiu; Ghicov, Andrei; Schmuki, Patrik (Physica Status Solidi-Rapid Research Letters, 2009)
In the present work we show that highly self-ordered iron oxide nanopores can be anodically grown to high aspect ratios, in optimized fluoride-containing ethylene glycol electrolytes. The as-formed layers are amorphous and contain a significant amount of fluorides. By annealing the layers can be crystallized and the fluorides can be removed. At elevated electrolyte temperatures the nanoporous system shows a transition to a nanotubular structure.
EAM Import::2019-03-13

Influence of anodization parameters on the expansion factor of TiO2 nanotubes - Albu, Sergiu; Schmuki, Patrik (Electrochimica Acta, 2013)
Growth of titania nanotubes was carried out in fluoride containing electrolytes using photolithographically defined thin film patterns to determine the amount of expansion when the metal is converted to oxide. This expansion of TiO2 nanotubes is studied for a large set of electrochemical conditions. We show that this parameter strongly depends on the applied anodization potential and the water content in the electrolyte whereas the fluoride content is only of minor influence. Expansion factors were found to vary between 1.3 and 2.8 depending on the anodizing parameters. This variation is explained in terms of efficiency of oxide growth, as well as of chemical composition, density, and porosity of the TiO2 nanotubular array.
EAM Import::2019-03-14

Morphological instability leading to formation of porous anodic oxide films - Hebert, Kurt R.; Albu, Sergiu; Paramasivam, Indhumati; Schmuki, Patrik (Nature Materials, 2011)
Electrochemical oxidation of metals, in solutions where the oxide is somewhat soluble, produces anodic oxides with highly regular arrangements of pores. Although porous aluminium and titanium oxides have found extensive use in functional nanostructures, pore initiation and self-ordering are not yet understood. Here we present an analysis that examines the roles of oxide dissolution and ionic conduction in the morphological stability of anodic films. We show that patterns of pores with a minimum spacing are possible only within a narrow range of the oxide formation efficiency (the fraction of oxidized metal atoms retained in the film), which should exist when the metal ion charge exceeds two. Experimentally measured efficiencies, over diverse anodizing conditions on both aluminium and titanium, lie within the different ranges predicted for each metal. On the basis of these results, the relationship between dissolution chemistry and the conditions for pore initiation can now be understood in quantitative terms.
EAM Import::2019-03-12

Preparation and Adsorption Properties of Pd Nanoparticles Supported on TiO2 Nanotubes - Honciuc, Andrei; Laurin, Mathias; Albu, Sergiu; Amende, Maximilian; Sobota, Marek; Lynch, Robert; Schmuki, Patrik; Libuda, Jörg (Journal of Physical Chemistry C, 2010)
Here we present preparation methods for a series of novel model heterogeneous catalysts consisting of Pd nanoparticles dispersed on self-organized TiO2 nanotube arrays (TiNTs). For a comprehensive comparative study of TiNTs' surface adsorption properties, different chemical and physical methods were employed for the deposition of the Pd nanoparticles: (i) e-beam deposition in high vacuum (HV) and (ii) in ultrahigh vacuum (UHV), (iii) impregnation, and (iv) metal precipitation. Following preparation, the Pd/TiNTs were exposed to several O-2 (oxidative) and CO (reductive) cleaning cycles at 500 K in UHV. After each cleaning cycle, the CO adsorption properties were systematically probed with time-resolved infrared reflection-adsorption spectroscopy to monitor the surface state of the catalyst. It is shown that clean and well-defined Pd/TiNT catalysts can be obtained, which are well suited for future adsorption and reactivity studies.

Thermal air oxidation of Fe: rapid hematite nanowire growth and photoelectrochemical water splitting performance - Grigorescu, Sabina Georgiana; Lee, Chong-Yong; Lee, Kiyoung; Albu, Sergiu; Paramasivam, Indhumati; Demetrescu, Ioana; Schmuki, Patrik (Electrochemistry Communications, 2012)
Different iron oxide structures were formed by annealing of iron foils in air at temperatures between 500 °C to 800 °C. Depending on temperature, a significant variation in the hematite/magnetite ratio and a strongly temperature dependent morphology is obtained. While over a wide range of conditions more or less compact Fe3O4/Fe2O3 layers are obtained, at 600 °C rapid growth (several micrometer per hour) of highly crystalline hematite nanowires can be observed. Visible light photocurrent measurements in 1 M NaOH under AM 1.5 100 mW/cm2 conditions show that photocurrent density and the onset potential for water oxidation strongly shifted in the cathodic direction for the nanowire morphology. The results indicate that a simple air oxidation of iron can provide a rapid path to form hematite nanowires. Obtained layers are considerably active as photoanodes for solar water splitting.
EAM Import::2019-03-12

Transport properties of single TiO2 nanotubes - Stiller, Markus; Barzola-Quiquia, Jose; Lorite, Israel; Esquinazi, Pablo; Kirchgeorg, Robin; Albu, Sergiu; Schmuki, Patrik (Applied Physics Letters, 2013)
We investigated the electric transport properties of single TiO2 nanotubes separated from an anodic titania nanotube array. The temperature dependence of the resistance measured with the conventional four point method of all investigated samples show a Mott variable range hopping behavior. The results obtained with two contacts indicate the existence of a potential barrier between the Cr/Au contacts and samples surfaces, which influence is clearly observable at temperatures <150 K. Impedance spectroscopy in the frequency range of 40 Hz to 1 MHz carried out at room temperature indicates that the electronic transport of these polycrystalline tubes is dominated by the grain cores.
EAM Import::2019-03-13